A comparison of the intelligibility of esophageal, electrolaryngeal, and normal speech in quiet and in noise. - Holley, Sandra Cavanaugh; Lerman, Jay W; Randolph, Kenneth (Journal of Communication Disorders, 1983)
The effect of different levels of a multiple-talker background noise on the intelligibility of normal, esophageal, and electrolaryngeal speech was investigated. A superior laryngectomized male speaker and a normal-age matched male speaker produced the speech stimuli used in the study. Audiotape recordings of the speakers were presented to panels of naive listeners. The data from the listeners' responses revealed significant differences in the intelligibility of normal, esophageal, and electrolaryngeal speech as a function of the background noise level. The data did not indicate a superiority of one form of alaryngeal speech over the other in adverse noise conditions. © 1983.
23 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1983QY97400007, lens.org/077-212-672-431-70X tex.type: [object Object]
Keywords: Adolescent; Adult; Comparative Study; Female; Human; Male; Noise; Phonetics; Speech Intelligibility; Speech; Alaryngeal; Speech; Esophageal; adolescent; adult; article; comparative study; dept.cmd; esophagus speech; female; human; male; methodology; noise; phonetics; speech intelligibility